A FRAMEWORK FOR LEARNING GEOGRAPHY ONLINE STRATEGY IN 21ST CENTURY LEARNING: A LITERATURE REVIEW - Nyokro Mukti Wijaya; Suhendro Suhendro (Journal Learning Geography, 2022)
The purpose of this research is to determine a strategic framework for learning geography online. The method used in research is literature studies with a qualitative approach. The data were collected from books, scientific journals, and relevant reading references related to this literature study. The results of this research show a strategic framework for learning geography online with a scientific approach starting from the planning stage, which is group permutation and choosing online learning platforms which are both synchronous (zoom or google meet) and asynchronous (whatsapp group or google classroom), stage of implementing online learning, which is applying scientific learning (observing, asking questions, gathering information, associating and communicating information) by combining online platforms which are synchronous and asynchronous then using the internet as sources of learning, and assessment stage, where three aspects are assessed, namely attitudes, knowledge, and skills. This research implies that technology-based or online learning should be implemented in learning activity, and it has become an obligation considering the changing times that prioritize technology.